A produção mundial da natureza e os agrotóxicos em Goiás – 2023: The global production of nature and pesticides in Goiás - 2023 - Batista da Silva, Edson; Mendonça Oliveira de Souza, Murilo; Caetano Fogaça, João Paulo (Revista Cocar, 2024)
O modelo de agricultura hegemônico se realiza por pacotes tecnológicos. Goiás, desde o pós-Segunda Guerra Mundial aderiu ao pacote tecnológico da “Revolução Verde”. Este artigo analisa o quadro dos agrotóxicos no estado e no município de Goiás, com atenção para formas de uso, comercialização e os efeitos não controlados do uso de venenos. Para tanto, se utilizou de pesquisa bibliográfica, documental e de campo. Os resultados apontam que Goiás é o quinto consumidor de agrotóxicos no Brasil, desdobramento correlato do avanço do agronegócio. No município de Goiás, a despeito da inexistência de credenciamento para comercialização de agrotóxicos, venenos são vendidos cotidianamente. Igualmente, como resultado não controlado da produção mundial da natureza pelos agentes capitalistas hegemônicos, os agrotóxicos eliminam as condições objetivas de realização da apicultura no município. Palavras-chave: Agrotóxicos; Natureza; Agronegócio. Abstract The hegemonic agricultural model is based on technological packages. Since the aftermath of the Second World War, Goiás has adhered to the "Green Revolution" technological package. This article intends to analyze the situation of pesticides in the state and municipality of Goiás, in Brazil, with a focus on their use, commercialization and the uncontrolled effects of the use of pesticides. To this end, the methodology was based on bibliographical, documentary and field research. The results indicate that Goiás is the fifth consumer of pesticides in Brazil, a development correlated with the advancement of agribusiness. In the municipality of Goiás, despite the lack of accreditation for the sale of pesticides, poisons are sold on a daily basis. Likewise, as an uncontrolled result of world production of nature by hegemonic capitalist agents, pesticides eliminate the objective conditions for carrying out beekeeping in the municipality. Keywords: Pesticides; Nature; Peasants; Agribusiness.